Selenium and male fertility - Maiorino, Matilde (Henry Stewart Talks, 2007)
Selenium in nutrition, Selenocysteine as the 21st aminoacid, Eukaryotic selenocysteine-containing proteins, GPx4 and the Sec-glutathione peroxidases, The redox chemistry of GPx4 and spermatogenesis, Selenium and male fertility, Whole body KO of GPx4, Selenoproteins involved in spermatogenesis, Spermatozoa GPx4 activity as a biomarker of fertility
Updated at 2016/08/31